2022
DOI: 10.1029/2022jb025106
|View full text |Cite
|
Sign up to set email alerts
|

A Rate‐, State‐, and Temperature‐Dependent Friction Law With Competing Healing Mechanisms

Abstract: Seismic activity is responsible for some of the most devastating natural hazards, frequently causing death and economic loss at tectonic hotspots worldwide. Natural earthquakes originate from a frictional instability propagating at high velocity, producing seismic waves. Seismic ruptures result from stick-slip on a frictional surface

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 195 publications
5
47
0
Order By: Relevance
“…Seismic swarms can be explained by temperature-hardening during shear heating that leads to apparent work-hardening (B. . (Tian & He, 2019), dry granite (Mitchell et al, 2016), and hornblende (Liu & He, 2020) synthetic gouges as well as shale (An et al, 2020) and other (den Hartog et al, 2021;Valdez et al, 2019) natural gouges can be explained by a single deformation mechanism with the competition between two thermally-activated healing mechanisms (Barbot, 2022). (b) Westerly granite (Blanpied et al, 1995(Blanpied et al, , 1998, basalt (Okuda et al, 2023), and Alpine Fault gouges (Niemeijer et al, 2016) require a second deformation mechanism to explain restrengthening at high temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seismic swarms can be explained by temperature-hardening during shear heating that leads to apparent work-hardening (B. . (Tian & He, 2019), dry granite (Mitchell et al, 2016), and hornblende (Liu & He, 2020) synthetic gouges as well as shale (An et al, 2020) and other (den Hartog et al, 2021;Valdez et al, 2019) natural gouges can be explained by a single deformation mechanism with the competition between two thermally-activated healing mechanisms (Barbot, 2022). (b) Westerly granite (Blanpied et al, 1995(Blanpied et al, , 1998, basalt (Okuda et al, 2023), and Alpine Fault gouges (Niemeijer et al, 2016) require a second deformation mechanism to explain restrengthening at high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…which may not be constant. The effective power-law exponent and activation energy vary with rock type and temperature, typically falling within the range of n = 10-170 and Q = 10-150 kJ/mol in the brittle field (Atkinson, 1984;Barbot, 2019bBarbot, , 2022. In granitoid rocks, the exponent decreases from n ≈ 140 at 300°C to n ≈ 10 at 600°C with the activation energy ranging from 80 ± 20 to 180 ± 50 kJ/mol depending on strain-rate (Pec et al, 2016).…”
Section: Constitutive Framework For Fault Frictionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other works have shown that RSF parameters might vary with the slip velocity (Mair and Marone, 1999), making them additional variables or dofs of the system (Im et al, 2020). Despite these and more recent works (e.g., Perfettini and Molinari, 2017;Barbot, 2022) our understanding of the seismic cycle and the number of dofs required to describe it are still unclear.…”
Section: Introductionmentioning
confidence: 99%